Vertical distribution of perfluoroalkyl substances in water columns around the Japan sea and the Mediterranean Sea. (September 2019) - Yamazaki, Eriko; Taniyasu, Sachi; Ruan, Yuefei; Wang, Qi; Petrick, Gert; Tanhua, Toste; Gamo, Toshitaka; Wang, Xinhong; Lam, Paul K.S.; Yamashita, Nobuyoshi
Abstract: Perfluoroalkyl substances (PFASs) have become an important class of global environmental contaminants, yet their vertical profile in the marine water column is still less understood, especially for the semi-closed seas. In this study, the contamination level and spatial distribution of 8 PFASs were investigated in both surface and vertical water samples from two semi-closed seas, the Japan Sea and the Mediterranean Sea. Similar levels and compositions of PFASs were found between these two seas. The vertical profile of PFASs in the Mediterranean Sea was variable while that was relatively steady in the Japan Sea, probably due to their different pollution sources. The accumulation rate of PFASs from the East China Sea to the Japan Sea was calculated, for which perfluorooctanesulfonic acid and perfluorooctanoic acid were found to have high accumulation potency in both surface and deep water; most of the investigated PFASs were accumulated in the deep water due to the long residence time while they were more likely to escape to the Pacific Ocean in the surface water. This work aimed (i) to study the distribution of PFASs in both surface and vertical water samples in two semi-closed seas, namely the Japan Sea and for the first time the Mediterranean Sea, (ii) to assess the temporal trend in the Japan Sea, and (iii) to firstly investigate the potential transport of PFASs from the East China Sea and Taiwan Strait in order to estimate the inventory of PFASs in whole water mass in the Japan Sea. Graphical abstract: Image 1 Highlights: A remarkable increase in PFASs levels was found in the Japan Sea from 2005 to 2010. The inventory of PFASs in whole water mass was firstly assessed in semi-closed sea. The annual ΣPFASs inflow from the East China Sea to the Japan Sea was around 70.8 t. The PFASs vertical profile in the Mediterranean Sea implied a few pollution sources. PFOA predominated in the Japan Sea, the Mediterranean Sea, and the East China Sea.